The effect of selenium and zinc on CD4(+) count and opportunistic infections in HIV/AIDS patients: a randomized double blind trial. Issue 3 (3rd May 2020) - Hadadi, Azar; Ostovar, Afshin; Edalat Noor, Behnaz; Rasoolinejad, Mehrnaz; Haji Abdolbaghi, Mahboobeh; Yousefi, Sahar; Khalili, Hossein; Manshoori, Gita; Khashayar, Patricia; Alipour, Zahra; Safari, Narges
ABSTRACT: Objectives : We assessed the effect of selenium and zinc supplementation on CD4 cell count and the risk of developing opportunistic infections. Methods : In a double blind clinical trial, 146 HIV(+) patients receiving combination antiretroviral therapy with CD4(+) >200/cubic millimeter were screened for comorbidities and opportunistic infections, and randomized to receive daily selenium (200 µg), zinc (50 mg) or placebo for 6 months, before a 3-month follow-up period. CD4 cell counts were measured in the 3 th, 6 th and 9 th months. The serum selenium and zinc were measured in the 6 th month. The incidence of opportunistic infection was assessed monthly for 6 months and at the end of the 9 th month. Results : The final incidence of supplement deficiency for placebo, zinc and selenium were 46.7%, 44.7% and 50.0%, respectively. Overall compliance with supplementation was 99.42%. Although the changes from baseline were not statistically significant, zinc supplementation was significantly associated with reduced risk of opportunistic infections. Conclusion : Development of the opportunistic infections after zinc supplementation significantly decreased; however, significant improvement in CD4 count was not observed in this group.